Metabolic, neuromuscular, and performance responses to graded carbohydrate ingestion during exercise - Newell, M. L. (2015)
A dose response relationship between carbohydrate (CHO) ingestion and exercise performance has not been consistently reported. Additionally the underlying metabolic and neuromuscular explanations for an improvement in performance with increasing doses of CHO have not been fully explained. In Chapter 2 of this thesis 20 male cyclists completed 2 h of submaximal exercise followed by a time trial task (531 ± 48KJ). Three CHO electrolyte beverages, plus a control (water), were administered during a 2 h ride providing 0, 20, 39 or 64 g CHO·h-1 at a fluid intake rate of 1 L·h-1. Performance was assessed by time to complete the time trial task, mean power output sustained, and pacing strategy used. Mean task completion time (min:sec ± SD) for 39 g·h-1 (34:19.5 ± 03:07.1, p=0.006) and 64 g·h-1 (34:11.3 ± 03:08.5 p=0.004) of CHO were significantly faster than control (37:01.9 ± 05:35.0). The mean percentage improvement from control was -6.1% (95% CI: -11.3 to -1.0) and -6.5% (95% CI: -11.7 to -1.4) in the 39 and 64 g·h-1 trials respectively. The 20 g·h-1 (35:17.6 ± 04:16.3) treatment did not reach statistical significance compared to control (p = 0.126) despite a mean improvement of -3.7% (95% CI -8.8 to 1.5%). These data demonstrate that consuming CHO at a rate between 39 to 64 g·h-1 is likely to be optimal for most individuals looking to utilise a single source CHO as an ergogenic aid during endurance performances lasting less than 3 hrs. Attempts have been made to try and understand the acute metabolic regulation that occurs when ingesting increasing amounts of CHO. However, no one study has fully investigated the metabolic mechanisms underlying graded increments of CHO ingestion. In Chapter 3 we aimed to utilise stable isotopes and blood metabolite profiles to examine the integrated physiological responses to CHO ingestion when ingested at rates throughout the range where performance gains appear greatest. Twenty well-trained male cyclists completed 2 h constant load ride (95% lactate threshold, 185 ± 25W) where one of three CHO beverages, or a control (water), were administered every 15 min, providing participants with 0, 20, 39 or 64 g CHO·h-1 at a fixed fluid intake rate of 1L·h-1. Dual glucose tracer techniques (6,6,2H2 glucose and U13C labelled glucose) were used to determine glucose kinetics and exogenous carbohydrate oxidation (EXO) during exercise. Endogenous CHO contribution was suppressed in the second hour of exercise when consuming 39 and 64 g·h-1 in comparison to 0 g·h-1 (-7.3%, 95%CI: -13.1 to -1.6 and -11.2%, 95%CI: -16.9 to -5.5 respectively). Additionally, consuming 64 g·h-1 suppressed the endogenous CHO contribution by -7.2% (95%CI: -1.5 to -13.0) compared to the 20 g·h-1 treatment. Exogenous CHO oxidation rate increased by 0.13 g·min-1 (95%CI: 0.10 to 0.15) and 0.29 g·min-1 (95%CI: 0.27 to 0.31) when consuming 39 and 64 g·h-1 in comparison to 20 g·h-1 of CHO. Peak exogenous CHO oxidation rates were 0.34 (0.06), 0.54 (0.09) and 0.78 (0.19) g·min-1 for 20, 39 and 64 g·h-1 respectively. Plasma NEFA concentration was 0.10 (95%CI: 0.07 to 0.13), 0.12 (95%CI: 0.10 to 0.16) and 0.16 (95%CI: 0.13 to 0.19) mmol.L-1 higher when consuming 0 g·h-1 in comparison to 20, 39 and 64 g·h-1 respectively. Both 39 and 64 g·h-1 were effective at sparing endogenous CHO stores of which it is estimated that most of this is liver glycogen sparing, but the measured response was highly variable between individuals. Consuming 39 g·h-1 of CHO appears to be the minimum ingestion rate required to have a significant metabolic effect that results in an increase in performance. Recent research has indicated a key role of endogenous CHO sensing and oral glucose sensing in maintaining central drive and peripheral function during endurance exercise tasks. Consuming 39 and 64 g·h-1 of CHO elicits the greatest improvements in performance and also demonstrate a similar metabolic response. The improvement in subsequent time trial performance when consuming 39 and 64 g·h-1 coincided with significant alterations in whole body substrate usage that lead to endogenous CHO sparing at the same ingestion rates. In Chapter 4 we aimed to utilise gold standard neuromuscular function assessment techniques, alongside novel measures, to investigate the effect of consuming different rates of CHO on neuromuscular function during and following prolonged cycling exercise. In a double-blind, randomised cross-over design, well-trained male cyclists (n=20, mean±SD, age 34 ± 10 y, mass 75.8 ± 9 kg, peak power output 394 ± 36 W, VO2max 62 ± 9 ml·kg-1·min-1) completed 2 familiarisation trials then 4 experimental trials. Trials involved a 2 h submaximal ride followed by a high intensity time trial task lasting approx. 35 min with each of 0, 20, 39 and 64 g·h-1 CHO ingestion rates during submaximal exercise. Each trial involved pre and post exercise assessments (MVC, Mwave twitch potentiation and force, motor unit recruitment and firing rate assessment using high density EMG) and during exercise (gross EMG amplitude). MVC peak torque values were reduced post exercise by -20.4 nM (95%CI: -26.5 to -14.4) in comparison to pre value on all trials with no differences between trials. The firing rates of early recruited motor units significantly increased by 1.55 pps (95%CI: 0.51 to 2.59) following exercise in comparison to pre-exercise rates. Gross EMG during the 2 h cycling bout revealed a main effect of treatment (p<0.01) but post hoc comparisons provided no clarity and likely reflect methodological issues. Consuming CHO at ingestion rates between 20 and 64 g·h-1 had little to no impact on the neuromuscular function of well-trained cyclists when comparing pre and post fatiguing exercise values. Despite differences in time trial completion time between trials, following exercise to fatigue in an endurance task, no post exercise differences were detected.